Analisis Teknik Modeling Dalam Layanan Bimbingan Kelompok Untuk Meningkatkan Self Esteem Pada Mahasiswa - Desti Nurlia; Rahma Aulia; Reza Dwi Rahmah; Imalatul Khairat (PT. Hasba Edukasi Mandiri, 2025)
This study aims to examine the use of modeling techniques in group counseling services as an effort to enhance self-esteem among university students. Using a qualitative approach through library research, this study reviews scholarly literature including journals, books, and theses related to self-esteem, modeling, and group guidance. Self-esteem plays a vital role in shaping students’ psychological well-being, influencing their confidence, academic performance, and social relationships. Modeling is a technique where individuals learn through observation and imitation of behaviors demonstrated by role models. In a group counseling setting, modeling offers real-life examples of positive behavior that participants can reflect upon and practice. The literature indicates that both single and multiple modeling approaches can significantly improve students' self-perception, self-regulation, and adaptive behavior. These processes help internalize a stronger sense of competence and self-worth. In addition, the group setting creates a supportive environment that fosters mutual learning, empathy, and emotional resilience. The findings suggest that incorporating modeling into group counseling is a promising strategy for promoting self-esteem among students.